2022
DOI: 10.7554/elife.77956
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoregulation of DSB-1 mediates control of meiotic double-strand break activity

Abstract: In the first meiotic cell division, proper segregation of chromosomes in most organisms depends on chiasmata, exchanges of continuity between homologous chromosomes that originate from the repair of programmed double-strand breaks (DSBs) catalyzed by the Spo11 endonuclease. Since DSBs can lead to irreparable damage in germ cells, while chromosomes lacking DSBs also lack chiasmata, the number of DSBs must be carefully regulated to be neither too high nor too low. Here, we show that in Caenorhabditis elegans, me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 97 publications
2
13
0
Order By: Relevance
“…Thus, we suggest that DSB induction in aged germlines is primarily repressed by signals caused from sperm depletion rather than reproductive aging, mating-induced signaling, or exposure to males. Multiple mutants in C. elegans have been reported to exhibit age-dependent decline in meiotic DSB induction [30,44,45]. Our research raises the possibility that these proteins may mediate or respond to signals from sperm.…”
Section: Sperm Depletion and Dsb Inductionmentioning
confidence: 64%
See 3 more Smart Citations
“…Thus, we suggest that DSB induction in aged germlines is primarily repressed by signals caused from sperm depletion rather than reproductive aging, mating-induced signaling, or exposure to males. Multiple mutants in C. elegans have been reported to exhibit age-dependent decline in meiotic DSB induction [30,44,45]. Our research raises the possibility that these proteins may mediate or respond to signals from sperm.…”
Section: Sperm Depletion and Dsb Inductionmentioning
confidence: 64%
“…Sperm depletion, but not absence of sperm, reduces DAF-16 nuclear localization in the intestine, indicating that loss of sperm has tissue-nonautonomous effects on IIS [49]. Notably, a recent study found that PP4 also maintains DSB induction in the C. elegans germline by promoting the dephosphorylation of the Rec114 homolog DSB-1 [45]. From this evidence, we propose that the influence of sperm depletion on DSB induction may be mediated through the IIS pathway.…”
Section: Plos Geneticsmentioning
confidence: 68%
See 2 more Smart Citations
“…Auxin-mediated protein depletion was performed as previously described (Guo et al, 2022; Zhang et al, 2015). Briefly, worms were transferred to bacteria-seeded plates containing 1 mM indole-3-acetic acid (Acros Organics, Cat #122160250) and incubated for the indicated time periods before analysis.…”
Section: Methodsmentioning
confidence: 99%